2005
DOI: 10.1016/j.eneco.2005.03.002
|View full text |Cite
|
Sign up to set email alerts
|

International market integration for natural gas? A cointegration analysis of prices in Europe, North America and Japan

Abstract: This paper investigates the degree of integration of natural gas markets in Europe, North America and Japan in the time period between the early 1990s and 2004. The relationship between international gas market prices and their relation to the oil price are explored through principal components analysis and Johansen likelihood-based cointegration procedure. Both of them show a high level of natural gas market integration within Europe, between the European and Japanese markets as well as within the North Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(108 citation statements)
references
References 13 publications
7
99
1
1
Order By: Relevance
“…The authors use cointegration analysis to show how unbundling pipeline ownership and capacity rights increased integration of regional spot prices in the United States. More recently, Siliverstovs et al (2005) use the Johansen test for cointegration to investigate relationships between European, Japanese, and North American gas prices. The authors find that European and Japanese gas prices are cointegrated but reject an absolute version of the law of one price, which would require that percent changes in European gas prices and Japanese LNG prices be one-for-one.…”
Section: Empirics: Cointegration and Lng Pricesmentioning
confidence: 99%
“…The authors use cointegration analysis to show how unbundling pipeline ownership and capacity rights increased integration of regional spot prices in the United States. More recently, Siliverstovs et al (2005) use the Johansen test for cointegration to investigate relationships between European, Japanese, and North American gas prices. The authors find that European and Japanese gas prices are cointegrated but reject an absolute version of the law of one price, which would require that percent changes in European gas prices and Japanese LNG prices be one-for-one.…”
Section: Empirics: Cointegration and Lng Pricesmentioning
confidence: 99%
“…It is found that there is a strong evidence of co-integration between the price of Brent oil and each of the European gas prices and between the price of WTI oil and each of the European gas prices at 1% significance level. Differently from the results of Siliverstovs (2005) and the multidimensional scaling analysis, the null hypothesis of no co-integration between European and Japanese gas markets is not rejected. Having found evidence of a co-integrating relationship, this implies causality in at least one direction.…”
Section: Findings and Discussionmentioning
confidence: 94%
“…The methodology part is based on the study of Siliverstovs et al (2005). The data covers the period of February 2000 to December 2010, totally 131 observations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oil indexed LTCs are also common for gas trade in continental Europe. The oil indexation explains, in part, why gas prices in Europe are fully integrated with oil prices (Asche et al, 2001;Asche et al, 2002;Asche et al, 2006;Siliverstovs et al, 2005;Panagiotidis and Rutledge, 2007). In markets where spot trade is more prevalent and gas-to-gas competition stronger, such as the US, the relationship between oil and natural gas prices tend to be much weaker (Villar and Joutz, 2006;Parsons and Ramberg, 2012).…”
Section: Background and Motivation: Natural Gas Tradementioning
confidence: 99%